Physical attractiveness and women’s intra-household bargaining power - Li, Zhongwu (Frontiers in Psychology, 2022)
This paper explores the role of physical attractiveness in affecting women’s intra-household bargaining power. The empirical analysis based on the China Family Panel Studies finds that physical attractiveness significantly increases women’s intra-household bargaining power. To solve the endogenous problem of physical attractiveness, we employ an instrument-variable-based regression to corroborate the conclusion. Using generalized structural equation model, we show that income, self-esteem, and interpersonal relationship are three possible transmission channels (or mediators) between physical attractiveness and women’s intra-household bargaining power.